Cell-type-specific transcription of prospero is controlled by combinatorial signaling in the Drosophila eye. - Hayashi, T.; Xu, C.; Carthew, R.W. (Development, 2008)
In Drosophila, Notch and Egfr signaling regulate the determination of many cell types, and yet how these common signals generate cell-specific transcription is not well understood. In the compound eye, prospero (pros) is transcribed specifically in R7 photoreceptors and cone cells. We show that the transcription of pros is activated by two visual-specific transcription selectors, Glass and Sine Oculis, that bind to an enhancer and promote its activation. Together with the pre-patterning transcription factor Lozenge, these factors work in a highly combinatorial manner, such that cells missing any one factor transcribe pros only weakly, if at all. However, the factors are not sufficient to activate the enhancer because of an additional requirement for both Notch and Egfr signals. The loss of Notch signaling produces a ;salt and pepper' effect, with some cells expressing near-normal levels and others expressing no detectable pros at all; thus, the signaling loss does not produce a uniformly reduced level of transcription activity in cells. This suggests a probabilistic mechanism, in which Notch signals influence the likelihood that the enhancer is inactive or fully active in any given cell. The activity level, therefore, is dictated by the proper combination of highly cooperative selector and pre-pattern factors present in the cell.